2014
DOI: 10.1016/j.theriogenology.2014.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal nutrient restriction followed by realimentation during midgestation on uterine blood flow in beef cows

Abstract: a b s t r a c tThe objective was to examine the effect of maternal nutrient restriction followed by realimentation during midgestation on uterine blood flow (BF). On Day 30 of pregnancy, lactating, multiparous Simmental beef cows were assigned randomly to treatments: control (CON; 100% National Research Council; n ¼ 6) and nutrient restriction (RES; 60% of CON; n ¼ 4) from Day 30 to 140 (period 1), and thereafter, realimented to CON until Day 198 of gestation (period 2). Uterine BF, pulsatility index (PI), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 24 publications
(35 reference statements)
1
10
2
1
Order By: Relevance
“…This adaptation may alter the functional potential of the placenta and thereby enable enhanced nutrient supply to the fetus during later gestation if maternal nutrition increases (Perry et al 1999). Doppler measurements of blood flow and uterine artery parameters from 120 dpc suggested that vascular supply to the placenta was similarly altered in the study animals once maternal diet treatment ceased , a scenario also reported in cows realimented following nutritional restriction in early gestation, whereby blood flow to the ipsilateral horn was increased following realimentation but not during the period of restriction (Camacho et al 2014).…”
Section: Placental Parametersmentioning
confidence: 64%
“…This adaptation may alter the functional potential of the placenta and thereby enable enhanced nutrient supply to the fetus during later gestation if maternal nutrition increases (Perry et al 1999). Doppler measurements of blood flow and uterine artery parameters from 120 dpc suggested that vascular supply to the placenta was similarly altered in the study animals once maternal diet treatment ceased , a scenario also reported in cows realimented following nutritional restriction in early gestation, whereby blood flow to the ipsilateral horn was increased following realimentation but not during the period of restriction (Camacho et al 2014).…”
Section: Placental Parametersmentioning
confidence: 64%
“…Additionally, offspring in the current study had the opportunity for compensatory growth during both fetal and postnatal stages before reaching the finishing period. For example, placental development and uterine blood flow in beef cows increase during realimentation following a period of nutrient restriction during early gestation (Vonnahme et al, 2007;Camacho et al, 2014), giving 1 possible time period for fetal compensatory growth. Although it is unclear if fetal development was altered by maternal nutrient restriction or RUP supplementation during early and midgestation in the current study, data here suggest that calves are able to overcome poor nutrient availability during early fetal development and perform similarly to offspring born to well-nourished dams during the finishing phase.…”
Section: Effects Of Maternal Dietary Treatment During Gestationmentioning
confidence: 99%
“…Uterine artery ultrasonography scans were performed in Experiment 2 as previously published (Camacho et al., ). Briefly, transrectal Doppler ultrasonography scans (Aloka SSD‐3500; Aloka America, Wallingford, CT, USA) were performed by positioning a linear finger probe (Aloka UST‐672; 7.5 MHz) dorsally in hand on the abdominal aorta, detecting the origin of the external iliac, and tracing this artery caudally to locate the internal iliac artery to establish the branch point of the uterine artery.…”
Section: Methodsmentioning
confidence: 99%